Electro deposition of thin films in the presence of complexing agent: A review - Ho, Soon Min (Research India Publications, 2015)
There are various types of thin films have been prepared by electrodeposition method in the presence of complexing agent. The properties of thin films were investigated using various tools such as scanning electron microscopy, x-ray diffraction, energy dispersive X-ray and UV-Visible spectrophotometer. The results indicated that the films were good quality thin films from an electrolyte that containing complexing agent.